THU0572 Heterogeneity of IGG4-Related Disease in Terms of Organ Damage, Treatment Response and Prognosis. (9th June 2015) - Yamamura, Y.; Matuura, I.; Nomura, Y.; Fujita, K.; Momoki, N.; Ueno, A.; Maruyama, K.; Hiramatu, M.; Yamamura, M.
Abstract : Background: IgG4-related disease (IgG4-RD) is characterized by IgG4 overproduction and various organ damage by IgG4-secreting plasma cells, but its long-term prognosis is unknown because of its new disease concept. Objectives: To determine long-term outcome of this chronic disease, we have prospectively observed patients who were newly diagnosed as IgG4-RD in our hospital since April 2011. Methods: A total of 33 patients, including 22 males and 11 females, were made a diagnosis as having IgG4-RD principally according to the 2011 Japanese comprehensive diagnostic criteria. The majority of them showed high concentrations of serum IgG4 (median 569mg/dL, range 140-2390 mg/dL), but only 8 patients were definite with IgG4+ cells >40% in the biopsy specimen. 16 patients showed IgG4+ cell tissue infiltration but failed to satisfy this histological definition. Nine patients who could not have biopsy were diagnosed by serum IgG >135 mg/dL plus diagnostic imaging. These patients have been prospectively followed up. Results: Patients were diagnosed as IgG4-RD at the average age of 71 (37-85) with the disease duration between 3 months and 9 years, showing various organ damage (salivary gland n=15, pancreas n=9, aorta/artery n=9, kidney n=9, retroperitoneum n=7, lacrimal gland n=6, thyroid gland n=6, lungs n=6, biliary duct n=4, prostate n=2, articulate n=1). 22 patients received immunosuppressive therapy because of major organ dysfunction, including periaortis (n=9), renal pseudotumor and interstitial nephritis (n=8), pancreatitis (n=8), retroperitoneal fibrosis (n=6), lung disease (n=5), thyroiditis (n=5), sclerosing cholangitis (n=3), and prostate swelling (n=2) (mostly overlapping). Glucocorticoids (GC) were first started with the average dose of 22.5 mg/day prednisolone (4 - 60mg/day), and immunesuppressants such as azathioprine (AZA) and methotrexate (MTX; switched from AZA due to hepatotoxicity) were later added in 11 patients (AZA for 11, MTX for 1) for disease relapse or GC tapering. All patients successfully responded to these therapy and subsequently, their IgG4RD have been mostly well controlled. The remaining 11 patients with minor organ damage (salivary gland lesion n=7, lacrimal gland lesion n=2, etc.) or contraindications to immunesuppression did not receive any treatment. While under observation, malignancies such as MALT lymphoma, lung cancer and colon cancer developed in 3 patients, one of whom died of lymphoma. In addition, 3 patients died of hemorrhage from duodenal ulcer, sepsis and aspiration pneumonia, respectively, in which the relationship to IgG4-RD or therapy were undetermined. Conclusions: The results indicate that patients with IgG4-RD are clinicopathologically heterogeneous depending on patient's age at onset, organs affected and underlining pathogenesis, but their responses to GC and immunosuppressants are generally well and the disease itself are controllable in the short-term. Its longer-term control, prognosis and relationship to malignancy should be determined. Disclosure of Interest: None declared